Pengaruh Metode Latihan Shooting Free Throw Tanpa Gangguan dan Shooting Free Throw dengan Mata Tertutup Terhadap Tes Shooting Free Throw Static dan Dynamic - saragih, roni yusuf (Jendela Olahraga, 2019)
ABSTRACTThe purpose of this research is to analyze and find out the free throw training method which is very influential on static and dynamic free throw shooting tests. Fifteen students who were the subject of the study will be pretested to determine division of a group free throw exercise without interruption, free throw exercise with eyes closed and the control group. In this research two test instruments will be used, namely static free throw test and free throw dynamic shooting test. Will be given exercise for 6 weeks of training for each group and treatment 3 times a week. Test result of paired sample t-test on the free throw shooting method with closed eyes show a significant influence on both variables free throw static shooting test variable and free throw dynamic shooting test, while uninterrupted free throw shooting groups show a significant effect on variables free throw throw shooting test and free throw dynamic shooting test but more influential free throw shooting test with closed eyes. From the data obtained it can be concluded that both experimental groups have an increase to improve the free throw static shooting test and free throw dynamic shooting test, although the average number of values is not the same, the free throw shooting method with closed eyes variable proved able to affect both dependent variables. This can be due to limited time and less treatment was only conducted for 6 weeks and 18 meetings.Keywords : static free throw shooting test,  dynamic free throw shooting test, free throw exercise without interruption, free throw exercise with eyes closed